Global Financial Stability Report, September 2011 : Grappling with Crisis Legacies. (Global Financial Stability Report; Global Financial Stability Report ;, 2011)
The September 2011 Global Financial Stability Report cautions that the risks to global financial stability have increased substantially in recent months, during which heavy public debt burdens and weak growth prospects in many advanced economies combined with a series of shocks to the global financial system. Emerging markets, despite brighter growth prospects, face the risk of sharp reversals and so must guard against the buildup of financial vulnerabilities. Moreover, as the crisis has moved into its fifth year, it has entered a new phase in which political differences within and across economies are impeding progress to address the legacies of the crisis. The Report examines how the ongoing low interest rate environment and high uncertainty are driving the asset allocations of long-term, real-money institutional investors. The Report also looks at variables that can act as advance indicators of financial crisis and examines how the use of countercyclical capital buffers can help to dampen destabilizing cycles.